Pengaruh Peer To Peer Lending Dan Literasi Keuangan Terhadap Kinerja Keuangan UMKM Di Kota Semarang - Alfina Arfianti, Vera; Sutapa; Anik, Sri; Mutoharoh (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2025)
The relationship between peer to peer lending and financial literacy has a primary function by influencing the financial performance of MSMEs in Semarang City. On the one hand, peer to peer lending provides financing options that are more easily accessible to MSMEs who often have difficulty in obtaining formal loans. However, without adequate financial literacy, MSME actors are at risk of mismanaging loans, such as choosing products with high interest rates or being unable to prepare a good payment plan. This can lead to financial problems such as bad debts or liquidity crises that hinder business growth. This study focuses on the analysis of the influence of peer to peer lending and financial literacy on the performance of MSMEs in Semarang City. The quantitative method with an explanatory research approach was chosen to describe the relationship between the variables studied precisely. The population in this study consisted of culinary MSMEs in Semarang City with a total of 3,291 with a sample of 100 MSMEs with the criteria of having been in business for more than 3 years with a minimum of 2 employees. The analysis shows that peer to peer lending and financial literacy have a significant impact on the financial performance of MSMEs in Semarang City and it is hoped that business actors can take part in financial training or education so that they can design capital management strategies, maximize the use of resources, and reduce financial risks more efficiently.